INTEGRATING TECHNOLOGY-BASED LEARNING IN ENHANCING STUDENTS’ INTEREST IN ENGLISH LANGUAGE LEARNING - Wilda Tuljannah; Suryani Suryani; Ugahara Ugahara (Getsempena English Education Journal, 2025)
The aim of this study was to explore students' interest in learning English using technology-based learning. This research uses mixed methods that collect data combining quantitative and qualitative data. Data was collected through direct observation and questionnaires distributed to students, which covered aspects such as motivation, involvement, and preferences for the use of technology in learning English. The participants consist of 28 students from SMA 1 Indrapuri. The data were analyzed using a combination of qualitative and quantitative techniques. Observation notes were examined through content analysis to identify patterns of student motivation, engagement, and responses to technology-based learning. Questionnaire data were processed using descriptive statistics and thematic coding to capture overall trends and reinforce the qualitative findings. The result from observation revealed the use of technology, such as PowerPoint and Quizziz, is able to create a more interactive and interesting learning environment, with increased active participation and student involvement. The result from questionnaire indicated that the majority of students had a positive view of using technology in learning English. 75.7% of students enjoyed learning English using technology and 77.1% students stated that technology made learning English more engaging. However, only 58.5% of students' showed awareness of the importance of English for their future. Although technology succeeded in increasing interest in learning, the findings also revealed that its impact was not felt equally by all students. Therefore, teachers need to integrate technology effectively to meet the diverse needs and preferences of students. This research concluded that the use of technology in English language learning has great potential to increase students' interest in learning. It requires adequate infrastructure and training for both teachers and students to maximize the use of this technology.